2006
DOI: 10.1103/physrevb.73.064424
|View full text |Cite
|
Sign up to set email alerts
|

Robust half-metallic antiferromagnetsLaAVOsO6andLaA

Abstract: We have theoretically designed three families of the half-metallic (HM) antiferromagnets (AFM), namely, LaAVOsO 6 , LaAMoTcO 6 and LaAMoReO 6 (A = Ca, Sr, Ba), based on a systematic ab initio study of the ordered double perovskites LaABB ′ O 6 with the possible B and B ′ pairs from all the 3d, 4d and 5d transtion metal elements being considered. Electronic structure calculations based on first-principles density-functional theory with generalized gradient approximation (GGA) for more than sixty double perovski… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 31 publications
6
63
0
Order By: Relevance
“…46 Noting the similarities 47 between relaxorferroelectrics and martensites the authors propose a model based on the fine-scale twinning of tetragonal ͑or rhombohedral͒ domains. In their model, the lattice parameters of the observed monoclinic and orthorhombic phases, derived from x-ray diffraction measurements with a finite beam size, are actually the volume-averaged parameters of the finely twinned tetragonal ͑or rhombohedral͒ phase.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…46 Noting the similarities 47 between relaxorferroelectrics and martensites the authors propose a model based on the fine-scale twinning of tetragonal ͑or rhombohedral͒ domains. In their model, the lattice parameters of the observed monoclinic and orthorhombic phases, derived from x-ray diffraction measurements with a finite beam size, are actually the volume-averaged parameters of the finely twinned tetragonal ͑or rhombohedral͒ phase.…”
Section: -4mentioning
confidence: 99%
“…Such a model is indeed in agreement with the experimental evolution of the lattice parameters as a function of electric field and temperature, which satisfy the required "invariance conditions." 45,46 Importantly, in the adaptive phase model, the piezoelectric response when a stress or electric field is applied along a nonpolar direction is inherently coupled to local ferroelastic domain wall motion, albeit on a very fine scale. That is, it will be irreversible wherever domain walls are pinned and Rayleigh-law hysteresis will be expected as a result.…”
Section: -4mentioning
confidence: 99%
“…In our case, the M C phase of BFO, has a hierarchical nanodomain structure, but consists of the same M C phase in both the stripe domains and the lamellar substructure, which is unlike the adaptive structure of the PMN-PT single crystals. Furthermore, the large tetragonal ratio (c/a = 1.25) in T-like M C phase of BFO wouldn't encourage a domains at large compressive stresses and we did not detect the a/c/a/c… type polydomain structure, which is reportedly in the adaptive domain picture proposed in cubiclike PMN-PT and PZT near their MPB compositions [20, 24,25]. The nanodomain walls in PMN-PT and PZT are along <110> or <100> direction [20,22] while, in BFO, the substructure nanodomain walls do not appear to have any principle crystallographic orientation.…”
mentioning
confidence: 47%
“…One also note that the LSAO substrate may not be completely removed in the relatively thick area of plan-view TEM sample and thus is still able to stabilize the M C phase. PT, besides a intrinsic monoclinic M C structure reported by Noheda et al [23], others suggested that the monoclinic phase could be an adaptive phase [24,25] where the tetragonal c/a nanodomains assembled together into submicrodomains, and thus the overall microdomain exhibited a monoclinic nature due to an averaging effect [20,24,25]. In our case, the M C phase of BFO, has a hierarchical nanodomain structure, but consists of the same M C phase in both the stripe domains and the lamellar substructure, which is unlike the adaptive structure of the PMN-PT single crystals.…”
mentioning
confidence: 99%
“…Recently, Wang 28 carried out a systematic analysis of the lattice parameters and their changes at the T − M C phase transition in PMN− xPT and PZN− xPT compositions near the MPB. This approach was based on three intrinsic relationships previously derived assuming an adaptive ferroelectric phase transformation: 19 there the lattice parameters of the intermediate M C phase were related to those of the T and C ones.…”
Section: Diagrams Of Domain Types and Interfaces In Heterophase mentioning
confidence: 99%